2016
DOI: 10.1093/cercor/bhw102
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Corticogenesis from Embryonic Stem Cells Recapitulates the In Vivo Epigenetic Control of Imprinted Gene Expression

Abstract: In vitro corticogenesis from embryonic stem cells (ESCs) is an attractive model of cortical development and a promising tool for cortical therapy. It is unknown to which extent epigenetic mechanisms crucial for cortex development and function, such as parental genomic imprinting, are recapitulated by in vitro corticogenesis. Here, using genome-wide transcriptomic and methylation analyses on hybrid mouse tissues and cells, we find a high concordance of imprinting status between in vivo and ESC-derived cortices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(61 citation statements)
references
References 84 publications
10
49
0
Order By: Relevance
“…The Bp ESC lines were E14Tg2a (hereafter E14) , WT‐B1 [19], and Tau‐eGFP ; the Ag‐ESC lines were AK2 and AG‐B6 [19]; the Pg‐ESC lines were PG‐BT6 and PG‐08–21 (both from Columbus, U.S.) and PR8 (from Cambridge, U.K.). E14 was maintained on gelatin and the six other lines were propagated on mitomycin‐treated MEFs in DMEM (Dulbecco's Modified Eagle Medium, Life Technologies, Courtaboeuf, France) supplemented with 15% ESC‐certified FBS (Life Technologies), 0.1 mM nonessential amino acids (Life Technologies), 1 mM sodium pyruvate (Life Technologies), 0.1 mM β‐mercaptoethanol (Sigma, Saint‐Quentin Fallavier, France), 50 U/ml penicillin/streptomycin (Life Technologies), and 10³ U/ml LIF (Millipore, Molsheim, France) as described . All ESC lines were regularly controlled to exclude the presence of mycoplasma using the Mycoalert kit (Lonza, Levallois‐Perret, France).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Bp ESC lines were E14Tg2a (hereafter E14) , WT‐B1 [19], and Tau‐eGFP ; the Ag‐ESC lines were AK2 and AG‐B6 [19]; the Pg‐ESC lines were PG‐BT6 and PG‐08–21 (both from Columbus, U.S.) and PR8 (from Cambridge, U.K.). E14 was maintained on gelatin and the six other lines were propagated on mitomycin‐treated MEFs in DMEM (Dulbecco's Modified Eagle Medium, Life Technologies, Courtaboeuf, France) supplemented with 15% ESC‐certified FBS (Life Technologies), 0.1 mM nonessential amino acids (Life Technologies), 1 mM sodium pyruvate (Life Technologies), 0.1 mM β‐mercaptoethanol (Sigma, Saint‐Quentin Fallavier, France), 50 U/ml penicillin/streptomycin (Life Technologies), and 10³ U/ml LIF (Millipore, Molsheim, France) as described . All ESC lines were regularly controlled to exclude the presence of mycoplasma using the Mycoalert kit (Lonza, Levallois‐Perret, France).…”
Section: Methodsmentioning
confidence: 99%
“…Oppositely, we found that Pg‐ESC imprinting was surprisingly Bp‐like. Next, Pg‐ESC lines were differentiated according to an established protocol of in vitro corticogenesis that reproduces the main features of in vivo corticogenesis , including the parent‐of‐origin dependent expression of imprinted genes . We found that Pg‐ESCs generated cortical‐like progenitors and electrophysiologically active glutamatergic neurons.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations